ERGONYMS-ELEMENTARY FUNCTIONS OF LANGUAGE - S. Ahmadaliyeva (Galaxy International Interdisciplinary Research Journal, 2022)
In this article of onomastics composition entering ergonomics based on harvest done etymological name and structural to face analysis is done